Procurement strategy selection for construction contract : an artificial neural network - 283142 Gan, Eng Toh; Razali Adul Hamid; National Convention Of Quantity Surveying in Malaysia (2001 : IIUM, Gombak, Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2001)
06